國際高等教育競爭力分析：以新加坡與韓國大學教師待遇與兼職制度為例 An Analysis of International Higher-Education Competitiveness: Taking the Treatment and Part-Time Employment Policies of Singaporean and South Korean University Teachers as Examples - 黃家凱 Chia-Kai Huang; 林侑毅 Yu-Yi Lin; 陳慶智 Qing-Zhi Chen (National Taiwan Normal University, 2022)
近年新加坡與韓國高等教育在世界大學排名表現卓越，兩國紛紛邀請世界優秀大學至國內設校，並透過彈性的高等教育人事制度，有效吸引國際優秀人才。本研究以個案研究法進行研究，並以新加坡兩所大學、韓國五所大學進行多重個案研究，系統化比較分析新加坡及韓國高等教育人事制度，並以大學教師待遇與兼職制度為例進行分析。研究結果顯示，在大學教師薪資待遇及留才政策方面，新加坡大學之薪資待遇具高度彈性，韓國則依國家法令實施，此外，彈性之競爭性薪資待遇結構有效增進兩國高等教育機構留才與攬才之競爭力。在大學教師兼職制度方面，新加坡與韓國在兼職定義、法規規範等各方面皆有不同之作法，對於違規兼職的法律效果亦有不同。本研究綜合研究結果提出三點結論：一、新加坡與韓國高等教育機構在人事制度規範上具有相當之自主性；二、彈性的高等教育機構人事制度有助於大學留才與攬才；三、多元的津貼補助有助於提升高等教育機構競爭力。最後，本研究提出建議，供作臺灣在高等教育人事制度方面，留才、育才及攬才之可行制度與策略，以及制度改革之參據。 Research Motives and Purposes Singapore and South Korea, two of the four Asian tigers (in addition to Hong Kong and Taiwan), both have gross domestic products (GDPs) per capita higher than that of Taiwan. In world university rankings, the higher education institutions of South Korea and Singapore exhibit strong performance, reflecting their high competitiveness and ability to attract outstanding talent. The compensation package is the key to an organization's recruitment and retention of talent, and is it also an essential motivating factor for employees to stay in the organization. Therefore, the compensation package provided by South Korean and Singaporean universities must be sufficiently attractive for attracting the aforementioned outstanding talent. Accordingly, this study investigated the influence of the personnel system regulations, the compensation package, and talent retention policies of South Korea and Singapore governments on their universities' ability to attract and retain talent as well as on the competitiveness of the universities. Through a systematic comparison and analysis of the personnel systems of Singaporean and South Korean universities and by taking the compensation package and part-time employment systems of their university faculty as examples, this study provides references for Taiwanese higher education institutions that can be used to formulate feasible personnel systems and human resource strategies to promote the retention, cultivation, and recruitment of talent. Research Methods This study adopted the multiple-case design and recruited cases from South Korea and Singapore. Specifically, this study focused on the analysis of university faculty's compensation package and part-time employment systems in South Korea and Singapore. The cases recruited in this study were from two universities in Singapore, including National University of Singapore and Nanyang Technological University and five universities in South Korea, including Pusan National University, Seoul National University, the University of Seoul, Korea University, and Sungkyunkwan University. The study also examined relevant regulations and documents of these univerisities for data triangulation. Research Results Regarding the university faculty's compensation package in Singapore and South Korea, the results of this study demonstrate the following: 1. The university faculty's compensation package in Singapore are highly flexible, whereas those of university faculty in South Korea are set in accordance with national laws and regulations. 2. A flexible and competitive compensation package can effectively promote the retention and recruitment of talent in higher-education institutions. Regarding regulations of the part-time employment of university faculty in Singapore and South Korea, the results demonstrate the following: 1. Higher education institutions have lenient definitions and regulations of the part-time employment of university faculty. 2. Higher education institutions are flexible about the competent authorities responsible for the approval of part-time work and about the relevant criteria. 3. The basic principle of part-time employment regulations in higher education institutions is to avoid conflicts of interest in all aspects, including the scope and criteria of part-time work institutions, the part-time work in for-profit or overseas institutions, and the termination of part-time work. 4. Higher education institutions adopt relatively lenient regulations regarding the scope of part-time employment in other institutions and the legal consequences of illegal part-time work. Conclusions and Suggestions By analyzing the faculty's compensation package, talent retention policies, and the faculty's part-time employment policies at two universities in Singapore and five universities in South Korea, this study comes to the following three conclusions: 1. Higher education institutions in Singapore and South Korea enjoy considerable autonomy regarding personnel system regulations. The Singapore government does not place excessive constraints or regulations on the personnel systems of higher education institutions; the universities are permitted to formulate such regulations on their own with a high degree of flexibility. Although South Korea has enacted a fundamental law to regulate relevant matters, the regulations established therein are lenient. In other words, national and public universities are permitted to formulate regulations flexibly within the constraints set by the law, thus enabling universities to maintain considerable autonomy. 2. Flexible personnel systems at higher education institutions promote the retention and recruitment of talent. The highly flexible and performance-oriented compensation package adopted by Singaporean universities effectively promote the retention and recruitment of outstanding faculty. South Korean higher education institutions employ competitive compensation package for part-time faculty, and their compensation package are determined by their performance and rankings. This enables the institutions to attract outstanding talent, thereby enhancing the competitiveness of higher education nationwide. 3. Diverse types of allowances and subsidies help attract and retain talent, thereby enhancing the competitiveness of higher-education institutions. The case study of the two aforementioned Singaporean universities revealed that both universities provide different types of subsidies and allowances for faculty from other countries. In addition to the basic salary, the aforementioned South Korean universities offer various types of nonfixed compensation for faculty. In particular, private universities are highly flexible in providing nonfixed compensation. Nonfixed allowances and subsidies help universities effectively retain talent. Based on the research results, this study proposes two suggestions for the reference of domestic law authorities in formulating regulations of the personnel systems of Taiwanese higher education institutions, as follows: 1. Encouraging faculty to take part-time jobs that are consistent with their regular work and the universities' interests. The Singaporean government does not impose explicit and compulsory regulations on the part-time employed of faculty employed by higher education institutions, and Singaporean universities are permitted to manage such matters independently. Although South Korea regulates the part-time employment of university faculty, the government allows for moderate flexibility instead of prohibiting part-time employment altogether. South Korean universities are permitted to formulate flexible regulations of part-time employment. We suggest that Taiwan government learn from the practices of Singapore and South Korea governments, allowing for greater flexibility for faculty wanting to work part-time as long as their part-time jobs are consistent with their regular work and the universities' interests.